The Great Wall of Surajpura - Srivastava, Roli (Migration Story, 2024)
Surajpura, Rajasthan: The villagers of Surajpura in Rajasthan have built a wall: a 15-feet mud bulwark that snakes through vast barren land for nearly a mile, with an equally long trench dug painstakingly beneath it. The soil even today appears loose but the wall passed its strength test last year when it arrested rainwater runoffs, and the trench channelled the water to parched farms in the drought-prone region, reviving them for the first time in over two decades.